The Experimental Study of Kinesthetic Style Student Learning Outcomes in Remedial Teaching Assisted by Projectile Motion Props - Sari Eka Putri; Iwan Permana Suwarna (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
The main problem of this study is that students who are not able to gain the minimum score were not given remedial teaching and learning that were adjusted to their learning style. This study aimed to determine the effect, improvement, and effectiveness of the use of projectile motion props in remedial teaching on kinesthetic style students learning outcomes and students’ response to the use of the props. The research method used in this study was a quasi-experiment with nonequivalent control group design. Hypothesis test results of the post-test results with the Mann-Whitney U test at the confidence level of 95% (α = 0.05) obtained the significance value (2-tailed) that was 0.000. Alternative research hypotheses (H1) were accepted (there were effects of projectile motion props on remedial teaching on kinesthetic style student learning outcomes). The kinesthetic style student in the experimental group successfully gained 0.64 (middle category) in their learning outcomes, and the controlled group students gained less only 0.31 (middle category) in their learning outcomes. In the cognitive domain of C2 (understanding), the experimental group students experienced the highest increase, which was 0.72, while the controlled group gained only 0.50. The effectiveness of remedial teaching in the experimental group was very effective (80%); meanwhile, in the controlled group, it showed ineffectiveness (28%). Students of kinesthetic style’s response are very good (81%) on the use of projectile motion props.